Unique Characteristics of Scientific and Technology Language in Lifebuoy Body Wash Packaging - Rosidin, Chintami; Tanjung, Nazahra Aulia Arifah; Natsir, Muhammad; Siholmarito, Tiurma; Anjelina, Nia (Retorika: Jurnal Komunikasi, Sosial dan Ilmu Politik, 2024)
This study explores the unique characteristics of scientific and technical terminology used on Lifebuoy Body Wash packaging. By looking at how technical terms, measurable statements, and creative descriptions are combined, the study shows how these components affect customer opinions, preferences, and product trust. This article clarifies the strategic nexus of marketing strategies and scientific communication by utilizing insights from previous research as well as a thorough examination of Lifebuoy's packaging. The results show that using scientific language helps to build credibility and dependability in the eyes of customers in addition to helping to distinguish the brand in a crowded market. Furthermore, the study underscores the pivotal role of packaging as a persuasive tool that bridges technical innovation with consumer engagement, ultimately shaping purchasing behaviors. These insights contribute to a deeper understanding of how brands leverage scientific discourse to enhance their market presence and establish a strong connection with their target audience.